1997
DOI: 10.1074/jbc.272.37.23206
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Two Heme B Centers in Cytochromeb 561 from Bovine Adrenal Chromaffin Vesicles as Revealed by a New Purification Procedure and EPR Spectroscopy

Abstract: We have established a new purification procedure of cytochrome b 561 from bovine adrenomedullary chromaffin vesicles. The heme content analysis of the purified sample indicated the presence of 1.7 molecules of heme B/cytochrome b 561 molecule. EPR spectroscopy of the purified enzyme in oxidized state showed that there were three types of low spin heme species. Two of them showed usual EPR signals at g z ‫؍‬ 3.14 and g z ‫؍‬ 2.84 arising from the same heme and were interconvertible depending on pH. The other sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
100
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(111 citation statements)
references
References 22 publications
(29 reference statements)
10
100
1
Order By: Relevance
“…Only CYBASC1 of wild watermelon was found targeted to the PM in GFP construct experiments with onion epidermal cells (Nanasato et al, 2005). Moreover, the optical spectra of bona fide cytochrome b561 (CYBASC1 in plants; Tsubaki et al, 1997;Bérczi et al, 2007) are characterized by an asymmetric a-band with a maximum close to 561 nm and a shoulder at 557 nm, unlike the cytochrome involved in trans-PM electron transport whose a-band is definitely symmetric (Asard et al, 1992). Overall, it is unlikely that cytochrome b561 (CYBASC1) represents a significant fraction of high-potential cytochromes b of plant PM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only CYBASC1 of wild watermelon was found targeted to the PM in GFP construct experiments with onion epidermal cells (Nanasato et al, 2005). Moreover, the optical spectra of bona fide cytochrome b561 (CYBASC1 in plants; Tsubaki et al, 1997;Bérczi et al, 2007) are characterized by an asymmetric a-band with a maximum close to 561 nm and a shoulder at 557 nm, unlike the cytochrome involved in trans-PM electron transport whose a-band is definitely symmetric (Asard et al, 1992). Overall, it is unlikely that cytochrome b561 (CYBASC1) represents a significant fraction of high-potential cytochromes b of plant PM.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochromes b561 are high-potential, transmembrane redox proteins of about 25 kD made of six membrane-spanning a-helices, which bind two hemes b. One heme is predicted to be close to an ascorbate binding site facing the cytosol, whereas the second heme faces the opposite side of the membrane and can be oxidized by either MDA or ferrichelates (Tsubaki et al, 1997;McKie et al, 2001;Bérczi et al, 2005;Kamensky et al, 2007). Plants contain several orthologous genes to animal cytochrome b561 Bashtovyy et al, 2003).…”
mentioning
confidence: 99%
“…It has been observed that recombinant and native plant and mammalian Cyts b 561 have characteristic Asc-reducible spectra (30,33,(41)(42)(43)(44). To confirm this biochemical characteristic for DCytb, the absorption spectra were measured using stripped membrane fractions from yeast cells expressing mouse DCytb (Fig.…”
Section: Evidence That Dcytb Is An Mdha Reductase In Humanmentioning
confidence: 99%
“…This cytochrome b is very similar to the chromaffin granule cytochrome b 561 ; not only the biochemical and spectrophotometric characteristics and the rather high redox potential values but also the transmembrane electron transporting capabilities of the two cytochromes b were similar (Asard, Horemans & Caubergs 1992, 1995a . On the basis of multiple alignment analysis and electron spin resonance measurements (Tsubaki et al 1997) it seems possible that the chromaffin granule cyt. b 561 has six trans-membrane segments, two distinct hemes and binding sites on opposite sides of the membrane for ascorbate and MDA.…”
Section: Hemesmentioning
confidence: 99%